Resistance mutations impair benzimidazole efficacy against Ascaridia galli by altering β-tubulin interactions - Jan Clyden Tenorio (Microbes and Infectious Diseases)
Background:  The emergence of benzimidazole resistance among helminths of veterinary and public health importance has been of grave concern. Benzimidazole resistance is caused by mutations (i.e., F167Y, E198A, and F200Y) that occur in the β-tubulin genes of helminths thereby affecting the structure of the expressed protein. This research aims to determine the effects of these canonical resistance-associated mutations on the in silico binding of A. galli β-tubulin and benzimidazole drug ligands. Methods: The β-tubulin amino acid sequence of A. galli was retrieved and edited to contain the resistance-associated mutations. These were used to model the tertiary structure of the protein. The in silico docking studies used the modeled proteins with benzimidazole drug ligands (i.e., Fenbendazole, Mebendazole, Oxfendazole, and Albendazole). The binding affinities (kcal/mol) and docking positions were examined. Results: The results show that resistance-associated mutations caused alterations in the binding interactions between the A. galli β-tubulin and benzimidazole drug ligand. The E198A mutation caused slight reductions in binding affinities and changes in the binding positions indicating its potential role in conferring benzimidazole resistance. Molecular dynamics simulations revealed that wild-type and mutated A. galli β-tubulins share comparable binding behavior with Fenbendazole. The binding free energies show that the E198A mutation caused decreased binding efficacy, potentially causing resistance. Conclusion: The E198A mutation causes weakening of the β-tubulin-benzimidazole interactions indicating its crucial role in conferring resistance in A. galli. The emergence of these benzimidazole resistance-associated mutations should be assessed in field isolates as they may negatively affect the efficacy of pharmacological interventions.